THE EFFECT OF PROFITABILITY, LIQUIDITY, INDEPENDENT BOARD OF COMMISSIONERS AND AUDIT COMMITTEE ON COMPANY VALUE - Tiara Estafania Saputri; Wiralestari; Salman Jumaili (Kajian Akuntansi, 2025)
Abstract. This study analyzes the effect of profitability, liquidity, independent board of commissioners, and audit committee on company value. The population in this study consists of companies in the industrial sector listed on the Indonesia Stock Exchange during the period 2021–2023. The sampling method used is purposive sampling. The sample in this study consisted of 47 companies observed over 3 years, and after outlier data was removed, the total sample amounted to 130. This study is a quantitative study using secondary data from the Indonesia Stock Exchange. The data analysis techniques used include descriptive statistics, classical assumption tests: normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Meanwhile, hypothesis testing was conducted using multiple linear regression analysis with IBM Statistical Product and Service Solution (SPSS) Version 27 software. The analysis results show that profitability, liquidity, independent board of commissioners, and audit committee simultaneously have a statistically significant effect on company value. However, when analyzed partially, only profitability, liquidity, and the audit committee significantly effect company value, while the independent board of commissioners has no significant effect on company value. These findings indicate that company value in the industrial sector is influenced by financial performance and internal governance, providing important insights for investors and company management.